2020
DOI: 10.1177/0894845320958076
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Family Socioeconomic Status and Career Outcomes: A Life History Perspective

Abstract: Based on the life history perspective, this study tested a serial mediation model in which family socioeconomic status (SES) related to person–job fit via resource scarcity, career exploration, and goal persistence. We expected that when seeking employment, higher SES students would perceive lower resource scarcity, and, in turn, adopt more adaptive career behaviors (i.e., career exploration and goal persistence) to maximize career success, which would then lead to better person–job fit upon graduation. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…However, few studies examined school setting differences. Meanwhile, CE was found to be associated with family socioeconomic status (SES), with students with higher SES having a higher CE level [48]. The present study is the first to investigate gender and school differences in CE among Chinese high-school students.…”
Section: Career Explorationmentioning
confidence: 72%
See 1 more Smart Citation
“…However, few studies examined school setting differences. Meanwhile, CE was found to be associated with family socioeconomic status (SES), with students with higher SES having a higher CE level [48]. The present study is the first to investigate gender and school differences in CE among Chinese high-school students.…”
Section: Career Explorationmentioning
confidence: 72%
“…This study also found that urban students had a significantly higher level in CE than rural school students. It was considered that students from urban schools had higher family SES than students from rural schools, and higher-SES students would perceive lower resource scarcity and in turn adopt more adaptive career behaviors such as CE [48]. For these reasons, career educators and researchers should consider the needs of rural school students and be mindful of the unique career behaviors of students from different backgrounds.…”
Section: School Difference In Career Exploration and Career Decision-making Self-efficacymentioning
confidence: 99%
“…As mentioned previously, there is evidence (Hu et al, 2020;Lehmann, 2019;Raque-Bogdan & Lucas, 2016) that the socio-economic status is an important influencing factor on employability and career aspirations for both, first-generation and continuing-generation students. This aspect needs further consideration for university students from a variety of different perspectives if these inequalities are to be better addressed in the future.…”
Section: Limitations and Need For Further Researchmentioning
confidence: 86%
“…Through environmental exploration, individuals gather information related to jobs, organizations, and occupations and make rational career decisions [31]. Researchers maintain that career exploration (in the form of both self-exploration and environmental exploration) plays a vital role for individuals in identifying suitable job opportunities, achieving better employment, and coping with difficulties and challenges in their career transitions [32][33][34].…”
Section: Career Explorationmentioning
confidence: 99%